Diversity and inclusion in libraries a call to action and strategies for success - Jones, Shannon D., 1974-; Murphy, Beverly, 1957- (Medical Library Association books., 2019)
This book explores some of the challenges that libraries and librarians face due to diversity and inclusion issues among library staff, as well as the patrons that they serve. Its goal is to increase awareness of and sensitivity to the social, cultural, and educational needs of everyone involved.